Enlisting Employees in Improving Payroll Tax Compliance: Evidence from Mexico - Kumler, Todd; Verhoogen, Eric; Frías, Judith (The Review of Economics and Statistics, 2020)
Comparing two sources of wage data in Mexico—firms' reports to the social security agency and individuals' responses to a household survey—we document extensive underreporting of wages by formal firms, with compliance better in larger firms. We also present evidence that the 1997 Mexican pension reform, which tied pension benefits more closely to reported wages for younger workers, led to a relative decline in underreporting for younger age groups. The results suggest that giving employees incentives and information to improve the accuracy of employer reports can be an effective way to improve payroll tax compliance.